Immunomodulatory interactions between mesenchymal stromal/stem cells and immune cells in psoriasis: therapeutic potential and challenges - Mohammadreza Dashti; Mojgan Mohammadi; Sajad Dehnavi; Mahvash Sadeghi (Stem Cell Research & Therapy)
Abstract Psoriasis is defined as a persistent autoimmune disease characterized by the appearance of psoriatic lesions on the surface of the skin. Currently, various approaches including chemicals, corticosteroids, phototherapy, and biological agents are being proposed and implemented to improve psoriatic lesions by modulating immune system activity or metabolic processes, often with unintended consequences and side effects. Currently, mesenchymal stromal/stem cells (MSCs) have attracted considerable interest among researchers due to their ability to modulate immune responses and their ease of application, representing a promising strategy for alleviating clinical symptoms in the treatment of allergic reactions, autoimmune diseases, cancer, and more. This study will investigate how MSCs interact with immune system cells involved in psoriasis development, such as neutrophils, keratinocytes, dendritic cells (DC), and T cell subtypes, for potential therapeutic use in psoriasis management. In this case, several immunomodulatory mechanisms are involved, including expression of chemokines, pro-inflammatory cytokines, matrix metalloproteinase and other factors involved in cell proliferation and neutrophil extracellular trap (NET) formation are among the effects of MSCs on keratinocytes and neutrophils. keratinocytes and neutrophils as pro-inflammatory cells involved in psoriasis pathogenesis and pathogenesis and progression of psoriasis. On the other hand, MSCs interact with DCs and various subsets of T cells, including Th1, Th2, Th17 and Tregs, to generate tolerogenic DCs and increase the differentiation of Tregs and modulate the Th17/Treg towards a regulatory state through overexpression of anti-inflammatory and immunomodulatory and immunomodulatory cytokines, including IL-10 and transforming growth Factor beta (TGF-β). Finally, we will focus on the challenges and obstacles in psoriasis treatment using MSCs, including limitations in the case of using MSCs from different sources and side effects that may be encountered by whole cell therapy strategies, which are attracting attention towards the implication of cell-free regimens such as using MSC-derived secretome or extracellular vesicles and exosomes to provide similar therapeutic outcomes without presumed side effects.